Aplikasi Edukasi “Music Traditional Arcade” Berbasis Android - David David; Andiny Rucitra; Fibriyenti Fibriyenti; Anthonio Anthonio (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The purpose of this study is to assist the government in introducing traditional music instruments in Indonesia to the community, especially teenagers aged from 16-20 years. Given increasingly in modern era makes people start to forget traditional music instruments and prefers modern music instruments. The method used in this research is literature study, observation, application design, and application testing that has been made. Result obtained from this study is an application that can meet the objectives of the study. The conclusion of this study is that the application gave elements and information about some traditional music instruments in interesting ways through mobile app game followed with attractive appearance and could be one way of helping the government to preserve traditional music instruments and provide insight into knowledge through the history of the instrument.